Imaging Corneal Stiffness with Optical Coherence Elastography - Kirby, Mitchell A. (My University, 2021)
Optical coherence elastography (OCE) can provide clinically valuable information based on local measurements of corneal stiffness. Corneal stiffness measurements may enable an individualized biomechanical model of the eye, monitor progression of ectatic changes in the cornea, and guide customized treatment plans. In this thesis, the physical structures which contribute to corneal biomechanical properties were described and a method presented to quantify elastic moduli responsible for corneal deformation using propagating elastic waves within the cornea. A fully non-contact system was developed to launch elastic waves using acoustic micro-tapping and track their propagation with phase-sensitive optical coherence tomography (OCT). A nearly incompressible transversely isotropic (NITI) model of corneal biomechanics was developed for accurate reconstruction of elastic moduli. The biomechanical reconstruction method was demonstrated in ex vivo porcine cornea and validated with conventional mechanical tests. This work provides a solid foundation which can be built upon to develop a non-contact, non-invasive clinical tool based on OCE to simultaneously map geometric (curvature and thickness) and elastic (Young’s modulus and additional shear modulus) properties of the cornea. Future applications of this work include the potential for pre-operative diagnostics and direct evaluation of post-operative outcomes in refractive correction surgeries.
Thesis (Ph.D.)--University of Washington, 2021
Keywords: Cornea; Elastography; Optical Coherence Tomography; Shear Modulus; Transverse Isotropy; Young's Modulus; Biomedical engineering; Biomechanics; Optics; Bioengineering